2012
DOI: 10.1016/j.jicc.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of coronary artery disease in a rural south Indian population on a governmental health insurance scheme

Abstract: PrevalenceCoronary heart disease a b s t r a c t Objectives: To examine the prevalence of Coronary heart disease (CHD) and associated risk factors based on coronary angiography among a geographically well-defined rural population of south India having an access to a governmental health insurance scheme.Study design: Observational cross-sectional study.Methods: This study in rural Andhra Pradesh covers 413 rural primary health centers each catering for 30,000 people was conducted between December 2007 and Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…In contrast, other studies showed that majority of the study participants were hypertensives. 4,7,15,18 In this study, majority of the cases and controls do not practice exercise regularly but no significant association was found with development of IHD. This is similar to study conducted by Mendagudali et al, Oommen et al at rural block of Vellore, Krishnan et al at rural block of Kerala and Dhungana et al at Sitapaila Village in Nepal.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In contrast, other studies showed that majority of the study participants were hypertensives. 4,7,15,18 In this study, majority of the cases and controls do not practice exercise regularly but no significant association was found with development of IHD. This is similar to study conducted by Mendagudali et al, Oommen et al at rural block of Vellore, Krishnan et al at rural block of Kerala and Dhungana et al at Sitapaila Village in Nepal.…”
Section: Discussioncontrasting
confidence: 61%
“…7,11 In contrast, studies done by others showed that majority of study participants had BMI >25 Kg/m 2 and study done by Dhungana et al showed that majority of the study participants had BMI in the range of 25-30. 4,14,18 The limitations of the present study were the sample size was small. Cases who have died are generally not taken and these may be systematically very different from living case as regards the exposure status and leads to survivorship bias.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is perhaps due to rapid epidemiological transition, increased life expectancy, lifestyle changes and genetic predisposition of Indians to atherosclerotic coronary heart disease (CHD). 3 The risk of CHD in Indians is 3-4 times higher than white Americans, 6 times higher than Chinese and 20 times higher than Japanese. Among adults over 20 year of age, the estimated prevalence of CHD is around3-4 per cent in rural areas and 8-10 per cent in urban areas, representing a two-fold rise in rural areas and a six-fold rise in urban areas between the years 1960 and 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps due to rapid epidemiological transition, increased life expectancy, lifestyle changes, and genetic predisposition of Indians to atherosclerotic coronary heart disease (CHD). [4] International Journal of Medical Science and Public Health 122 2018 | Vol 7 | Issue 2…”
mentioning
confidence: 99%